2021
DOI: 10.3389/ijph.2021.583613
|View full text |Cite
|
Sign up to set email alerts
|

Transport to School and Mental Well-Being of Schoolchildren in Ireland

Abstract: Objectives: We explored whether modes of transport (cycling, walking, public transport or private vehicle) between home and school are associated with mental well-being in children aged 10–17 years, participating in the Irish Health Behaviour in School-aged Children (HBSC) study.Methods: Scores on the World Health Organization Well-being Index and the Mental Health Inventory five-item versions, self-reported life satisfaction, happiness with self, body satisfaction, excellent self-rated health, and multiple he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The willingness or interest to study affects children's performance and cognitive ability in school (Golle et al, 2022; Ouyang et al, 2021). In Ireland, it was found that the mode of transport to school was associated with the mental well‐being of schoolchildren, which can have consequences on their WTS or go to school (Költő et al, 2021). WTS also helps to build self‐esteem, mental soundness, and emotional understanding of children.…”
Section: Methodsmentioning
confidence: 99%
“…The willingness or interest to study affects children's performance and cognitive ability in school (Golle et al, 2022; Ouyang et al, 2021). In Ireland, it was found that the mode of transport to school was associated with the mental well‐being of schoolchildren, which can have consequences on their WTS or go to school (Költő et al, 2021). WTS also helps to build self‐esteem, mental soundness, and emotional understanding of children.…”
Section: Methodsmentioning
confidence: 99%
“…A study comprising nine upper‐middle‐ or high‐income countries found that adolescents who cycled to school were less likely to report mental health complaints than passive commuters 21 . In contrast, similar findings of an Irish study attenuated to null after adjusting for sociodemographic confounders 22 . In low‐ and middle‐income countries, AST has been associated with lower odds of depression symptoms 23,24 and fewer suicide attempts 25 .…”
Section: Introductionmentioning
confidence: 95%
“…26 Additionally, none of the European studies have used a cohort that comprises a substantial population proportion of their countries. 21,22 To strengthen the previous PA and mental health literature, we examine associations of weekly leisure-time moderate-to-vigorous physical activity (MVPA) and AST with mental health outcomes using data from the nationwide School Health Promotion (SHP) study in Finland. We hypothesize, based on existing evidence, that both higher levels of leisure-time MVPA and AST are positively associated with mental health among 15-to 16-year-old adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations